Evaluation of state administration performance in improving access to education in rural areas of Indonesia - Daniel T Todapa (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Indonesia faces significant challenges in providing equitable access to education, particularly in rural areas. The disparities in access to educational services between urban and rural areas in Indonesia are varied, encompassing social, economic, and cultural aspects. The objective of this study is to evaluate the performance of state administration in enhancing access to education in rural areas of Indonesia. The research methodology employs a Study Literature Review (SLR)  techniques, starting with coding and categorization. Researcher then conduct thematic analysis by identifying thematic patterns emerging from the literature. Synthesis and interpretation from various literature sources are then performed to provide a comprehensive overview of the state's administrative performance. The research findings indicate that the government must continuously develop inclusive policies, ensure adequate budget allocation, conduct effective supervision and evaluation, and encourage active community participation. Based on the literature review on the role of state administration in improving access to education in rural areas of Indonesia, this article highlights the importance of targeted educational policies, efficient resource allocation, and robust performance evaluation mechanisms. Programs such as SM-3T and PIP are essential in addressing educational disparities by placing teachers in rural areas and providing financial support to students from low-income families.